PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SUBTEMA 1 KEKAYAAN SUMBER ENERGI DI INDONESIA - Amalia Septian Pandani; Tustiyana Windiyani; Mira Mirawati; Dadang Kurnia (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
THE EFFECT OF THE APPLICATION OF THE DISCOVERY LEARNING OUTCOMES OF SUB-THEME 1 OF THE WEALTH OF ENERGY SOURCES IN INDONESIAThe Effect of “Application Influence Discovery Learning Model on Learning Outcomes Subtheme 1 Wealth Energy Sources in Indonesia". The approach taken is quasi-experimental design of two groups at State Elementary School 2 Cikidang Cikidang District, Sukabumi Regency which consists of 66 students, This research was conducted in the even semester of the 2020/2021 academic year. The results of the study show that there is an "Influence" Application of the Discovery Learning Model to the Learning Outcomes of Subtheme 1 Wealth of Energy Resources in Indonesia. This can be seen from the N-Gain in experimental class group of 71, while the class group control gets an N-Gain value of 47. Complete learning outcomes obtained by the experimental group is 100% while in control class group by 88%. As well as the results of hypothesis testing that H0 is rejected and Ha is accepted because tcount (6.9204) ttable (1.9966). With this it can be concluded that the research has a positive influence and significant between "The Influence of the Application of the Discovery Learning Model" On Learning Outcomes of Subtheme 1 Wealth of Energy Resources in Indonesia". The results of this study are expected to provide new knowledge regarding the application of learning models that innovation can improve learning outcomes.